Agrohydrological analysis of groundwater recharge and land use changes in the Pampas of Argentina - Kroes, Joop; van Dam, Jos; Supit, Iwan; De Abelleyra, Diego; Veron, Santiago Ramón; de Wit, Allard; Boogaard, Hendrik; Angelini, Marcos Esteban; Damiano, Francisco; Groenendijk, Piet; Wesseling, Jan; Veldhuizen, Ab (Elsevier, 2019)
This paper studies the changes of groundwater, climate and land use in the Pampas of Argentina. These changes offer opportunities and threats. Lowering groundwater without irrigation causes drought and successive crop and yield damage. Rising groundwater may alleviate drought as capillary rise supports root water uptake and crop growth, thus narrowing the difference between potential and actual yields. However, rising groundwater may also limit soil water storage, cause flooding in metropolitan areas and have a negative impact on crop yields. Changing land use from continuous soy bean into crop rotations or natural vegetation may decrease groundwater recharge and thus decrease groundwater levels. In case of crop rotation however, leaching of nutrients like nitrate may increase. We quantified these impacts using integrated dynamic crop growth and soil hydrology modelling. The models were tested at field scale using a local dataset from Argentina. We applied distributed modelling at regional scale to evaluate the impacts on groundwater recharge and crop yields using long term weather data. The experiments showed that threats arise from continuous monotone land use. Opportunities are created when a proper balance is found between supply and demand of soil water using a larger differentiation of land use. Increasing the areas of land use types with higher evapotranspiration, like permanent grassland and trees, will contribute to a more stable hydrologic system with more water storage capacities in the soil system and lower groundwater levels. Modelling tools clearly support the evaluation of the impact of land use and climate change on groundwater levels and crop yields.